Breaking the logjam : obstacles to forest policy reform in Indonesia and the United States - Barber, Charles Victor; Johnson, Nels C.; Hafild, Emmy.; World Resources Institute (Washington, DC : World Resources Institute, 1994)
The book examines the origins and impacts of current forest policies and recommend ways to make forest management more sustainable in two of the most important forested countries
Includes bibliographical references: p. 109-120.
osc 29/01/2019
Loans
Keywords: Forest policy; Sustainable forestry